Validation of preimplantation genetic tests for aneuploidy (PGT-A) with DNA from spent culture media (SCM): concordance assessment and implication - Baoli Yin; Huijuan Zhang; Juanke Xie; Yubao Wei; Cuilian Zhang; Li Meng (BMC, 2021)
Abstract Background Spent culture medium (SCM) as a source of DNA for preimplantation genetic tests aneuploidy (PGT-A) has been widely discussed. Methods Seventy-five blastocysts that were donated for research provided a unique possibility in which multiple specimens, including trophectoderm (TE) biopsy, SCM, and paired corresponding whole blastocyst (WB) specimens from the same blastocyst source, could be utilized for the purpose of this preclinical validation. Results To conduct a validation ploidy concordance assessment, we evaluated the full chromosomal concordance rates between SCM and WB (SCM-to-WB), and between TE and WB (TE-to-WB) as well as sensitivity, specificity and overall diagnostic accuracy. 78.67% (59/75) of NGS results in the SCM group were interpretable, a significantly lower percentage than their corresponding TE and WB groups. This discrepancy manifests itself in intrinsically low quantity and poor integrity DNA from SCM. Subsequently, remarkable differences in full concordance rates (including mosaicism, and segmental aneuploidies) are seen as follows: 32.2% (SCM-to-WB, 19/59) and 69.33% (TE-to-WB, 52/75), (p < 0.001). In such cases, full concordance rates were 27.27% (15/55) in SCM-to-WB, and, 76% (57/75) in TE-to-WB (p < 0.001). Collectively, the NGS data from SCM also translated into lower sensitivities, Positive Predictive Value (PPV), Negative Predictive Value (NPV), overall diagnostic accuracies, and higher Negative Likelihood Ratio (NLR). Conclusions Our study reveals that DNA is detectable in the majority of SCM samples. Individual chromosomal aberration, such as segmental aneuploidy and mosaicism, can be quantitatively and qualitatively measured. However, TE still provides a more accurate and reliable high-throughput methodology for PGT-A. Meanwhile, cell-free DNA in SCM reporting lacks uniform diagnostic interpretations. Considering that this test is meant to determine which embryos are relegated to be discarded, PGT-A with cell-free DNA in SCM should not be permitted to be applied in routine clinical settings for diagnosis purpose.